Measurement of CP asymmetry in B0s→Dminus plusK± decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
We report the measurements of the CP -violating parameters in B s 0 → D s ∓ K± decays observed in pp collisions, using a data set corresponding to an integrated luminosity of 3.0 fb−1 recorded with the LHCb detector. We measure Cf = 0.73 ± 0.14 ± 0.05, A f ΔΓ = 0.39 ± 0.28 ± 0.15, AΔΓf¯¯¯=0.31±0.28±0.15Af¯ΔΓ=0.31±0.28±0.15 A_{\overline{f}}^{\varDelta \varGamma }=0.31± 0.28± 0.15 , Sf = −0.52 ± 0.20 ± 0.07, Sf¯¯¯=−0.49±0.20±0.07Sf¯=−0.49±0.20±0.07 S_{\overline{f}}=-0.49± 0.20± 0.07 , where the uncertainties are statistical and systematic, respectively. These parameters are used together with the world-average value of the B s 0 mixing phase, −2βs, to obtain a measurement of the CKM angle γ from B s 0 → D s ∓ K± decays, yielding γ = (128 − 22 + 17 )° modulo 180°, where the uncertainty contains both statistical and systematic contributions. This corresponds to 3.8 σ evidence for CP violation in the interference between decay and decay after mixing. Open image in new window